Factors influencing workplace satisfaction and retention of paediatric and child health clinical officers in Malawi's public health sector: a mixed-methods study - Farzana Yasmin; Peter Moons; Ajib Phiri; Sebastian Appelbaum; Laurine Nserebo-Banda; Carsten Krüger; Ralf Weigel; Yamikani Chimalizeni (Rural and Remote Health)
Introduction: Malawi's paediatric and child health workforce faces a critical shortage. In response, the Kamuzu University of Health Sciences has been training clinical officers (29 to date) in a Bachelor of Science in Paediatric and Child Health (BSc PCH) program since 2012 to serve as paediatric and child health district leaders in mostly rural areas. However, little is known about their workplace reality, and how it affects their fulfilment professionally, and such information may have policy implications. Therefore, we aimed to investigate Malawian BSc PCH clinical officers' workplace satisfaction, retention and influencing factors. Methods: In a mixed-methods, sequential, explanatory design study, we used a quantitative workplace satisfaction survey (five-point Likert scale) covering 11 dimensions, and qualitative in-depth interviews. Analysis included paired t-tests applied to Herzberg's two-factor theory of individual needs dimensions contributing to workplace satisfaction. During data collection in 2022, a total of 27 (93%) clinical officers participated in the survey, and 15 clinical officers and 14 key informants participated in in-depth interviews. Results: BSc PCH clinical officers worked at public district hospitals (n=13), public central hospitals (n=8), and at non-governmental organisations (NGOs) (n=6). Moral satisfaction and workplace/team harmony dimensions scored highest with means of 3.94±0.50 and 3.85±0.69, respectively. In contrast, career advancement and salary and benefits scored lowest with 2.01±0.99 and 2.46±0.80, respectively. Differences existed between clinical officers at public district hospitals compared to public central hospitals for the dimensions of tasks (eg variety, job description clarity) (p=0.034), work environment (p=0.006), and salary and benefits (p=0.032). Similarly, clinical officers at public district hospitals vs NGOs differed for the work environment (p=0.016), management style (p=0.003), and salary and benefits (p=0.002). Seventeen clinical officers considered leaving their current position, with salary being a significant reason (p=0.048). Moreover, delayed recognition and promotion, non-specific job descriptions, limited professional development opportunities, a lack of supervision, and career advancement barriers obstructed workplace satisfaction, according to the in-depth interviews. Conclusion: BSc PCH clinical officers program graduates' workplace satisfaction differs according to the workplace. Graduates working in public hospitals at district level, located mostly in rural areas, appear to be most critically affected and may leave government services. Changes in their specific work environment, career and professional development and remuneration may offer stakeholders opportunities to improve BSc PCH clinical officers' workplace satisfaction and retain them where they are needed most.